A Review of Loveless’s (2019) How to Make Art at the End of the World: A Manifesto for Research-Creation - Frank, Nicollette (Art/Research International)

(untitled) (University of Alberta, 2021)
This piece is a review of Natalie Loveless’s How to Make Art at the End of the World: A Manifesto for Research-Creation (2019). Poetic responses frame a more traditionally structured review. In her book, Loveless draws upon a diverse combination of theories to collage an argument for a care-full ethic in the increasingly neoliberal university. Her manifesto positions research-creation as an opportunity to reframe the narrative of research and pedagogy by going beyond what we study and attend to questions of how and why.